Illusory correlation and cognitive processes a multinomial model of source-monItoring - Bulli, Francesco; Primi, Caterina (2006)
The present research examines how the application of a multinomial source-monitoring model in the illusory correlation paradigm (Klauer & Meiser, 2000) can shed light on the cognitive processes underlying illusory correlation paradigm in children. A source-monitoring analysis allows the assessment of the roles of different factors (item memory, source memory and response bias) involved in the illusory correlation. In line with the previous source-monitoring analyses on adults (Klauer & Meiser, 2000; Meiser & Hewstone, 2001), illusory correlation phenomenon was caused by the guessing bias in source discrimination: a larger proportion of positive than negative behaviors was attributed to the majority group in a state of memory uncertainty. The results are discussed in terms of previously proposed theories of illusory correlation paradigm